Peran Aljabar Boolean dalam Ilmu Komputer dan Perancangan Rangkaian Logika - Puspitasari, Norma; Mayrohmah, Silvi Hindun (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Boolean algebra has made major contributions to computer science, especially in areas such as logic gate modeling, simplification of microprocessor circuits, geographic information systems, and digital circuits. Boolean algebra is used to analyze and simplify digital circuits, as well as in applications such as computer programs, geographic information systems, and digital circuits. This research is library research, namely by studying, researching and investigating and studying scientific works presented in the form of thesis books or papers that are relevant to the research topic. Some implementations of Boolean Algebra in Computer Science and Logic Circuit Design are Logic Programming and Logic Gates. Boolean algebra provides an essential theoretical foundation in computer science. Boolean algebra is essential in computer science, from the creation of logic circuits to recent advances in computing.